2003
DOI: 10.1016/s1010-7940(03)00413-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health-related quality of life and functional capacity following coronary artery bypass graft surgery

Abstract: Elderly patients not only have higher mortality and morbidity but also derive less benefit from CABG regarding certain aspects of QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
3
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 19 publications
10
68
3
3
Order By: Relevance
“…The findings of our study are consistent with findings of some of the earlier studies that reported a general improvement in HRQOL following cardiac surgery [6,9,14]. Our results show a statistically significant improvement for the whole study population in 4 domains of HRQOL: physical functioning, role-physical, social functioning and mental health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of our study are consistent with findings of some of the earlier studies that reported a general improvement in HRQOL following cardiac surgery [6,9,14]. Our results show a statistically significant improvement for the whole study population in 4 domains of HRQOL: physical functioning, role-physical, social functioning and mental health.…”
Section: Discussionsupporting
confidence: 92%
“…The operation has an impact on overall physical and mental health status and health-related quality of life (HRQOL); the patient's perspective and satisfaction are one of the major indicators of their medical outcome. In recent years, several studies have been undertaken to evaluate the patient's assessment of their general health status following cardiac surgery in order to help clinicians identify which patients are likely to have an improvement or decrement in their overall quality of life following surgery [6][7][8][9][10][11][12][13][14][15][16]. Most of these studies had reported an improvement in general health status, but there were some diversities related to age, different dimensions of health, preoperative functional status, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are similar to a number of other investigations that report improvements in health-related quality of life after cardiac surgical procedures as measured with a number of different quality-of-life instruments. [25][26][27] Jarvinen and colleagues 25 reported improvements in quality of life and functional capacity among CABG patients 1 year after surgery with the use of the RAND-36 Health Survey. Welke and colleagues 26 reported improvements in physical functioning and mental function 6 months after isolated CABG with the Short Form-36.…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
“…This type of surgery has been slightly modified since its initial publications 40 years ago and is associated with a morbidity rate of around 15%, including infection, cerebrovascular accident, bleeding, low-output syndrome, pulmonary complications and atrial fibrillation [13][14][15][16] . Regarding the postoperative follow-up, there have been reports of decreased physical capacity after sternotomy 17,18 and some patients have chest pain for up to one year after the surgery 19,20 . Minimally-invasive coronary artery bypass grafting is a surgery performed through a small incision on the left side, from where the surgeon has comfortable access to the aorta, the left internal thoracic artery and the anterior, lateral and even posterior coronary branches of the left ventricle, thus allowing the full operation without the need for opening the sternum 21 .…”
Section: Introductionmentioning
confidence: 99%